How universities teach cybersecurity courses online: a systematic literature review - Ahmed, Ali; Watterson, Craig; Alhashmi, Saadat; Gaber, Tarek (Frontiers in Computer Science, 2024)
IntroductionDistance learning has seen a significant increase as educational institutions have shifted toward offering online courses. Although some institutions quickly adapted, many struggled to modify traditional materials for online learners. Time was crucial for institutions lacking experience in remote teaching. Designing engaging online cybersecurity modules for diverse students is a major challenge. With the growing popularity of online courses, it is necessary to examine the teaching methods used. This paper presents a systematic literature review on the current state of online cybersecurity education at universities. Using the PRISMA approach, the study identifies prevalent themes and addresses key research questions. This study aims to analyze academic articles to highlight key findings on how universities teach cybersecurity courses online.MethodsThe authors conducted a systematic review of scholarly articles, adhering to the PRISMA approach for the period from January 2010 to August 2024. PRISMA offers a structured approach to planning, executing, and reporting systematic reviews in various fields, including healthcare and social sciences.ResultsThe review revealed several key findings on the design of online cybersecurity courses. Learner-centered approaches were commonly used, featuring active learning and practical applications. Effective instructional methods included collaborative learning, case studies, and simulations, which promoted student engagement and critical thinking. Universities emphasize practical skills evaluation and knowledge acquisition through project-based assessments. The role of IT tools was highlighted, with virtual laboratories, gamification, and simulations providing hands-on experiences, enhancing motivation, and facilitating active learning.DiscussionThis systematic review provides a comprehensive overview of the current online cybersecurity education practices in online universities. As a pioneering effort, it offers educators and curriculum developers valuable insight into designing effective online cybersecurity programmes to enhance teaching and learning practices. The review of online cybersecurity education highlighted several key findings. Learner-centered approaches, which incorporate active learning practices and practical applications, were prevalent. Effective instructional methods included collaborative learning, case studies, and simulations, which fostered student engagement and critical thinking. Assessments focused on the acquisition of practical skills and knowledge, using project-based tasks, practical exercises, and online quizzes. IT tools played a significant role, with virtual laboratories, gamification, and simulation environments that enhanced hands-on experiences, motivation, and active learning.